All Slot‐Die Coated Non‐Fullerene Organic Solar Cells with PCE 11%. (29th January 2021) - Chaturvedi, Neha; Gasparini, Nicola; Corzo, Daniel; Bertrandie, Jules; Wehbe, Nimer; Troughton, Joel; Baran, Derya
Abstract: Slot‐die (SD) coating is used to fabricate fully solution processed organic solar cells (OSCs) based on a blend of high performance donor polymer (PTB7‐Th) and a non‐fullerene acceptor (IEICO‐4F) for stable devices over extended periods of operation. The optimization of a sequential deposition process of transport and active layers, under ambient conditions, enable high efficiency slot‐die coated solar cells with remarkable power conversion efficiencies (PCE) > 11.0% to bridge the gap between lab‐to‐fab. Fully slot‐die coated inverted OSCs are demonstrated with efficiencies reaching 11% along with 1 cm 2 devices, proving the scalability and reproducibility of the proposed technique. Further, replacing the evaporated Ag electrode with solution processed Ag nanowire (AgNW) electrodes shows the highest light utilization efficiency of 5.26% for semi‐transparent OSC with a PCE of 9.07% and average visible transmission of 58%. Abstract : Slot die coating is used to fabricate high efficiency (power conversion efficiencies (PCE) > 11.0%), stable organic solar cells based on a donor PTB7‐Th and nonfullerene acceptor IEICO‐4F. The 11% small area and 1 cm 2 devices with a PCE of 9.63% show the scalability of the technique. The highest light utilization efficiency of 5.26% with a PCE of 9.07% is achieved for the all solution processed semi‐transparent solar cell.